Cowpea demand and supply patterns in West Africa: the case of Nigeria - Kormawa, P.; Manyong, Victor; Chianu, J. (2002)
Cowpea is an important source of protein in the diet of many West Africans. As a result of research focused on supply-side factors, the share of cowpea production among various grain legumes in Nigeria has increased since 1988, making Nigeria the largest cowpea producing country in the world. Most of the cowpea produced is used for direct consumption in both urban and rural areas. Though relevant for food production and policy planning purposes, there are very few data on the demand factors for cowpea. This paper analyzes cowpea production trends and estimates consumption patterns in Nigeria using weekly consumption data from 960 households in three major cities. The paper also highlights regional and seasonal price variations as well as the likely supply gaps in the year 2015 with possible options for increasing production to satisfy demand.